A Cross-Lagged Study of Developmental Trajectories of Video Game Engagement, Addiction, and Mental Health - Krossbakken, Elfrid; Pallesen, Ståle; Mentzoni, Rune Aune; King, Daniel Luke; Molde, Helge; Finserås, Turi Reiten; Torsheim, Torbjørn (Frontiers in Psychology, 2018)
Objectives: Video game addiction has been associated with an array of mental health variables. There is a paucity of longitudinal studies investigating such associations, and studies differentiating addicted gaming from problem and engaged (i.e., frequent but non-problem) gaming. The current explorative study investigate the natural course of gaming behavior in three sub-studies. The aim of study 1 was to investigate antecedents and consequences of video game addiction measured as a unidimensional construct (pathological gaming). Aim of study 2 was to investigate the same associations in terms of typologies of gamers (“engaged”, “problem”, “addicted”). Furthermore, study 3 aimed to investigate the estimated stability and transitions occurring between the aforementioned typologies, and a non-pathological gaming group. Methods: A nationally representative sample of 3000 adolescents aged 17.5 years was drawn from the population registry of Norway in 2012 and invited to participate in annual surveys spanning three years (NT1 = 2059, NT2 = 1334, NT3 = 1277). The respondents completed measures of video game addiction, depression, anxiety, loneliness, aggression and alcohol use disorder. Statistical analysis comprised cross-lagged path modelling, Satorra-Bentler chi square test (study 1), regression analyses (study 2), hidden Markov model of transition probabilities (study 3). Results: Findings in study 1 showed that depression and loneliness were reciprocally associated with pathological gaming. Physical aggression was identified as an antecedent, and anxiety was a consequence of pathological gaming. Investigation of the three typologies of gamers (study 2) identified loneliness and physical aggression as antecedents, and depression as a consequence of all typologies. Depression was found to be an antecedent of problem and engaged gamers. Loneliness was found as a consequence of problem gamers, and anxiety was a consequence of addicted gamers. High alcohol consumption was found antecedent to addicted gamers, and low alcohol consumption was found antecedent to problem gamers. The estimated stability of video game addiction was 35%. Conclusion: A reciprocal relationship between pathological gaming and measures of mental health problems seems to exist. The stability of video game addiction indicates a condition that for a substantial number of people does not resolve spontaneously over the course of two years.